Vulnerable The Law, Policy and Ethics of COVID-19 - Flood, Colleen M.; MacDonnell, Vanessa; Philpott, Jane (University of Ottawa Press / Les Presses de l'Université d'Ottawa, 2020)
Vulnerable examines the vulnerabilities and interconnections brought to light by the pandemic, as well as the legal, ethical and public policy responses. This book exposes the vulnerabilities of individuals, institutions, governance and legal structures, in several countries and worldwide.